Tethering of Telomeres to the Nuclear Envelope Is Mediated by SUN1-MAJIN and Possibly Promoted by SPDYA-CDK2 During Meiosis - Wang, Guishuan; Wu, Xiaolong; Zhou, Liwei; Gao, Sheng; Yun, Damin; Liang, Ajuan; Sun, Fei (Frontiers in Cell and Developmental Biology, 2020)
During meiosis, telomeres attach to the nuclear envelope (NE) to promote homologous chromosome moving, pairing, synapsis, and recombination. The telomere-NE attachment is mediated by SUN1, TERB1-TERB2-MAJIN (TTM complex) and TRF1. The interaction of the TTM complex with shelterin is mediated by TERB1 and TRF1, but how SUN1 interacts with the TTM complex is not yet fully understood. In this study, we found that SUN1 not only interacted with TERB1 but also interacted with MAJIN, and the interaction of SUN1 with MAJIN is stronger than TERB1. We also found that SUN1 interacted with SPDYA, an activator of CDK2. The binding sites of MAJIN and SPDYA at SUN1 were mapped and both MAJIN and SPDYA bound to the N-terminal domain of SUN1 and the two binding sites were close to each other. Furthermore, SPDYA bound to SUN1 via the Ringo domain and recruited CDK2 to SUN1. Then, we found that the interaction of SUN1 with MAJIN was decreased by the CDK2 inhibitors. Taken together, our results provide the possible mechanism of SUN1, MAJIN and SPDYA-CDK2 in promoting the telomere-NE attachment during meiosis.